MEWUJUDKAN SISTEM HUKUM INTEGRATIF: Harmonisasi Hukum Islam dan Hukum Adat Dalam Sistem Hukum Nasional - Al-Farabi (LPPM STAI DARUSSALAM LAMPUNG, 2013)
The pluralism of law which is applying, that is Islamic law and customarylaw, has not found the related point to go to the integral law yet. It is becauseof till now in the Republic of Indonesia is using system of national law whichbased on several system of law that has a various pattern. That third systemsof law are applying in Indonesia for a long time and dinamic. In early era,before colonialism, the relation of both addressed to pattern of integrationwith level of different coalescence in every sphere. The come of colonizermade a mark on the furthermore era with the pattern that reducted theapplying law (Islam and custom) in Nusantara step by step till the top withapplying a theory of reception. Furthermore, by reaching freedom, slowlythe system of national law took role in developing and rearranged law inNusantara, in other words, developing the theory of codification.To make that various law be able to be commander in living nationally andstately needs to be balanced the comprehension of national law which isintegral. The mean of it in this writing is finite to the idea to see the systemof national law like a law that makes a system of law of custom, Islam, andwest as a source and reality of history which proportionates with the realexperience of nation from early its existence till now, so that, to be nationallaw, Islamic and customary laws are signed not to be incompatible with thephilosophy of national law, and also, the system of national law ought torepresentate the value which lives and run by society.